2014
DOI: 10.1002/2014gl059246
|View full text |Cite
|
Sign up to set email alerts
|

Global distribution and seasonal dependence of satellite‐based whitecap fraction

Abstract: Key Points:• Seasonal dependence of global satellite-based whitecap fraction is presented • Results are compared to parameterized estimates and differences quantified • Implications of results for modeling air-sea processes are discussed Supporting Information:• Readme • Figure S1 Correspondence to:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

4
4

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 53 publications
(73 reference statements)
3
39
0
Order By: Relevance
“…Grythe et al (2014) noted a strong influence of sea surface temperature on sea spray aerosol production when they compared existing sea spray aerosol source functions with a global database of sea spray aerosol mass concentration measurements. Salisbury et al (2014) noted large differences between a commonly used whitecap fraction parameterisation (Monahan and O'Muircheartaigh, 1980) derived almost entirely in low-latitude regions and a satellite estimate derived over the entire globe. The authors postulate that the weaker wind speed dependence observed in their global data set may in part be due to the influence of secondary factors that co-vary with the wind geographically, such as sea surface temperature.…”
Section: Introductionmentioning
confidence: 89%
See 2 more Smart Citations
“…Grythe et al (2014) noted a strong influence of sea surface temperature on sea spray aerosol production when they compared existing sea spray aerosol source functions with a global database of sea spray aerosol mass concentration measurements. Salisbury et al (2014) noted large differences between a commonly used whitecap fraction parameterisation (Monahan and O'Muircheartaigh, 1980) derived almost entirely in low-latitude regions and a satellite estimate derived over the entire globe. The authors postulate that the weaker wind speed dependence observed in their global data set may in part be due to the influence of secondary factors that co-vary with the wind geographically, such as sea surface temperature.…”
Section: Introductionmentioning
confidence: 89%
“…Salter et al (2014) have shown that the interfacial bubble flux and bubble size spectra are strongly dependent on water temperature and that these are strongly correlated to total particle number flux in a laboratory setting. Grythe et al (2014) noted a strong influence of sea surface temperature on sea spray aerosol production when they compared existing sea spray aerosol source functions with a global database of sea spray aerosol mass concentration measurements.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There remains, however, an order of magnitude uncertainty in the parameterization of the whitecap fraction, and there is increasing evidence that neither the production of aerosol per unit area whitecap nor the lifetime of a whitecap are independent of the scale of wave breaking or other water properties (Norris et al, 2013a;Callaghan, 2013;Spada et al, 2013;Salter et al, 2014b;Salter et al, 2015). Recent work on satellite retrievals of the whitecaps (Anguelova and Webster, 2006;Gaiser, 2011, 2013) shows significant promise as a means of providing this driving parameter for sea spray source functions and implicitly accounting for the wide range of important controlling factors in addition to wind speed (Salisbury et al, 2013(Salisbury et al, , 2014. It might also ultimately allow a source function to be specified directly in terms of the satellite measurements.…”
Section: User Requirements For Marine Aerosol Particle Emissionsmentioning
confidence: 99%
“…There remains, however, an order of magnitude uncertainty in the parameteriza-660 tion of the whitecap fraction, and there is increasing evidence that neither the production of aerosol per unit area whitecap nor the lifetime of a whitecap are independent of the scale of wave breaking or other water properties (Norris et al (2013a); Callaghan (2013); Spada et al (2013), Salter et al (2014Salter et al ( , 2015). Recent work on satellite retrievals of the whitecaps (Anguelova and Webster, 2006;Gaiser, 2011, 2013) shows significant promise as a means of providing this driving 665 parameter for sea spray source functions, and implicitly accounting for the wide range of important controlling factors in addition to wind speed (Salisbury et al, 2013(Salisbury et al, , 2014. It might, also, ultimately allow a source function to be specified directly in terms of the satellite measurements.…”
Section: User Requirements For Emissions: Marine Aerosol Particlesmentioning
confidence: 99%